A manual training course. The selection and arrangement of exercises in wood, forge, and foundry work - Broom, Byron (My University, 1906)
Introduction: The general order and sequence of arrangement of these subjects and the, exercises involved in each is of fundamental importance in the selection of manual training courses. It is the purpose of this treatise, to show the relation between these different lessons, together with reasons for the sequence of exercises outlined. Woodwork should naturally come first as it is simpler, involving the use of simpler tools and softer materials, and is thus a better subject in which to teach the mathematics of dimensions, and the interpretation of plans, than are the metals. The forge work may not be so difficult if the student first masters woodwork. Also the philosophy of the behavior of iron and steel and the working conditions to be fulfilled in iron work, would place forging after the joinery course. The joinery course should also precede the course in turning because (1) It is a good preliminary training in the interpretation of plans. (2) It forms a foundation for the turning course as the workman acquires the knowledge of the behavior of the grain of wood when muscular force is applied to it. (3) It teaches how to apply this force to the best advantage, and (4) The use of simple tools should be mastered before commencing the operating of machinery. In woodwork soft wood should be practiced on before hard wood and provision has been made for this in setting forth the following lists of exercises. After joinery, turning, and forging, should come the foundry practice. Foundry work requires much care and still more knowledge of the action and reaction of materials and adaptation of means to an end than blacksmithing.
Citation: Broom, Byron. A manual training course. The selection and arrangement of exercises in wood, forge, and foundry work. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Foundry; Woodwork; Forge; Joinery; Training Manual; Theses